Rhodium-Catalyzed Double Isocyanide Insertion via a Vinylcarbodiimide Intermediate for the Synthesis of 2H-Pyrrol-2-imines - Wang, Yunlong; Li, Zongyang; Zhao, Haiying; Zhang, Zhenhua (Synthesis, 2019)
2H-Pyrrol-2-imine is an important structural motif exhibiting in biologically active compounds and natural products. An efficient rhodium-catalyzed one-pot reaction of one vinyl azide with sequentially with two different isocyanides is reported, which offers an alternative facile access to 3-amino-5-aryl-2H-pyrrol-2-imines bearing various substitution on the nitrogens in good yields. An unstable vinylcarbodiimide is the key intermediate in this cascade reaction.
Keywords: vinyl azide; vinylcarbodiimide; 2H-pyrrol-2-imine; isocyanide; palladium catalysis